2012
DOI: 10.1523/jneurosci.0532-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Tbr2 Is Essential for Hippocampal Lineage Progression from Neural Stem Cells to Intermediate Progenitors and Neurons

Abstract: Neurogenesis in the dentate gyrus has been implicated in cognitive functions including learning and memory, and may be abnormal in major neuropsychiatric disorders such as depression. Dentate neurogenesis is regulated by interactions between extrinsic factors and intrinsic transcriptional cascades that are currently not well understood. Here we show that Tbr2 (also known as Eomes), a T-box transcription factor expressed by intermediate neuronal progenitors (INPs), is critically required for neurogenesis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 50 publications
12
141
1
Order By: Relevance
“…This phenotype appears to be similar to that observed in the embryonic neocortex, where the loss of Tbr2 in INPs was shown to affect INP proliferation, leading to reduced production of neocortical pyramidal neurons (Arnold et al, 2008;Sessa et al, 2008). In addition, Tbr2 has been shown to promote neuronal lineage progression from NSC to INP, in part via the repression of Sox2 [SRY (sex determining region Y)-box 2], a key determinant of NSC identity (Hodge et al, 2012b). Interestingly, Tbr2 was recently found to also be expressed in Cajal-Retzius cells in the developing DG, and it is important for establishing and maintaining the radial processes of radial glial cells to facilitate the migration of newborn neurons (Hodge et al, 2013).…”
Section: Neuronal Differentiation Genessupporting
confidence: 69%
See 2 more Smart Citations
“…This phenotype appears to be similar to that observed in the embryonic neocortex, where the loss of Tbr2 in INPs was shown to affect INP proliferation, leading to reduced production of neocortical pyramidal neurons (Arnold et al, 2008;Sessa et al, 2008). In addition, Tbr2 has been shown to promote neuronal lineage progression from NSC to INP, in part via the repression of Sox2 [SRY (sex determining region Y)-box 2], a key determinant of NSC identity (Hodge et al, 2012b). Interestingly, Tbr2 was recently found to also be expressed in Cajal-Retzius cells in the developing DG, and it is important for establishing and maintaining the radial processes of radial glial cells to facilitate the migration of newborn neurons (Hodge et al, 2013).…”
Section: Neuronal Differentiation Genessupporting
confidence: 69%
“…Loss of Tbr2 in the intermediate neuronal progenitor (INP) population during DG neurogenesis resulted in decreased granule cell neurogenesis due to INP depletion (Hodge et al, 2012b). This phenotype appears to be similar to that observed in the embryonic neocortex, where the loss of Tbr2 in INPs was shown to affect INP proliferation, leading to reduced production of neocortical pyramidal neurons (Arnold et al, 2008;Sessa et al, 2008).…”
Section: Neuronal Differentiation Genessupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, it is likely that Dnmt1 inhibits p21 and p57 expression through such histone modification. In this context, recent studies have indicated that enzymes for histone deacetylation and methylation are involved in silencing p21 and p57 expression, respectively (Hsieh et al, 2004;Yang et al, 2009). Supporting these observations, we found that the loss of Dnmt1 decreased H3K27me3 in the p21 and p57 promoters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved through multiple spatiotemporally regulated developmental processes involving NSC migration, differentiation, and morphological change (Altman and Bayer, 1990a, b;Li and Pleasure, 2005). Accumulating studies indicate that cooperation between extracellular cues and intrinsic transcription factors is necessary for each step in DG development (Li and Pleasure, 2005;Shen et al, 2006;Hodge et al, 2012). For example, Wnt and bone morphogenetic protein signaling induce expression of the homeodomain transcription factor Emx2, whose deletion impairs the production and migration of neuronal progenitors (NPs) during embryonic DG development (Theil et al, 2002;Oldekamp et al, 2004).…”
Section: Introductionmentioning
confidence: 99%